Manajemen Bencana Di Badan Penanggulangan Bencana Daerah Kabupaten Luwu Timur - N, Faisal; Muhammadiyah, Muhammadiyah; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2022)
This study aimed to determine disaster prevention, disaster mitigation, preparedness, and response to BPBD in Disaster Management in East Luwu Regency. This study used qualitative with descriptive research type. The number of informants in this study were 4 people. The data collection techniques used observation, interview and documentation. Based on the results regarding that all indicators related to disaster management had been running well, it was shown in line with what was conveyed and what was accomplished from the results of observations as well as from public statements. This was supported by the existence of various programs, activities, and socialization that were carried out well and implemented and the community was also working together with the Government in this case the East Luwu Regency Disaster Management Agency in dealing with disasters that occured in East Luwu Regency, and support from several agencies in East Luwu Regency. But there were still some things that needed to be improved so that in the future everything could run optimally.Keywords: disaster management, disaster management agency